The Influence of Budget Planning And Budget Implementation On The Level of Budget Absorption - Hutagalung, Mulky Alrasi; Nurbaiti, Nurbaiti; Lubis, Arnida Wahyuni; Nurlaila, Nurlaila; Inayah, Nurul (International Journal Of Economics Social And Technology, 2024)
This research aims to (1) determine the effect of budget planning on the level of budget absorption at BAPPEDA Medan City, (2) determine the effect of budget implementation on the level of budget absorption at BAPPEDA Medan City and (3) determine the effect of budget planning and budget implementation on the level of budget absorption at BAPPEDA Medan City. This research method is quantitative research. The population and sample in this study were heads and employees at BAPPEDA Medan City, totaling 50 respondents. Data collection techniques use questionnaires. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 22.0 software. The research results show that first, budget planning partially has a positive and significant effect on budget absorption with a calculated t value of 3.754 > t table 2.012 and a significance value of 0.000 < 0.05. Second, partial budget implementation has a positive and significant effect on budget absorption with a calculated t value of 3.493 > t table 2.012 and a significance value of 0.001 < 0.05. Third, budget planning and budget implementation simultaneously have a positive and significant effect on budget absorption with a calculated F value of 11.772 > F table 3.20 and a significance value of 0.000 < 0.05.